Adam Fox – Daniel Woolf (eds.): The Spoken Word. Oral Culture in Britain 1500-1850.: Manchester University Press, Manchester – New York 2002, 286 s. - Janeček, Petr (Lidé města, 2008)
A review of the book by Adam Fox and Daniel Woolf.